1994
DOI: 10.1179/bjo.21.1.33
|View full text |Cite
|
Sign up to set email alerts
|

A Critique of Bond Strength Testing in Orthodontics

Abstract: The literature contains a large number of publications on in vitro bond strength testing of materials used in orthodontics. The results are often quoted by manufacturers to support their products. Little attention has been paid to the detail of the test procedures used. However, a review of the literature revealed a large variation in the methods used for bond strength testing in orthodontics making comparison of papers difficult and often impossible. The case for a possible standard technique is suggested. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
132
0
10

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(172 citation statements)
references
References 66 publications
4
132
0
10
Order By: Relevance
“…The reliability of adhesion between the CAD/CAM materials and the brackets in conjunction with the studied conditioning methods were further investigated with the Weibull analysis, which provides information regarding the probability of bracket failure [38]. The results indicated drastically higher (almost 8 to 10-fold) reliability with the feldspathic ceramic with both condition methods that signifies less reliable results with all new CAD/CAM materials (0.82-1.83) tested.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of adhesion between the CAD/CAM materials and the brackets in conjunction with the studied conditioning methods were further investigated with the Weibull analysis, which provides information regarding the probability of bracket failure [38]. The results indicated drastically higher (almost 8 to 10-fold) reliability with the feldspathic ceramic with both condition methods that signifies less reliable results with all new CAD/CAM materials (0.82-1.83) tested.…”
Section: Discussionmentioning
confidence: 99%
“…However, a lack of standardization in the methods used for bond strength testing in Orthodontics makes comparison of different studies difficult and often impossible (12). Studies are different in direction of force used in mechanical testing (9), sample storage time before mechanical testing (3,13), cross-head speed (3,8,9,13), tested materials (9,13) and tooth type (3,7,8,10,13).…”
Section: Discussionmentioning
confidence: 99%
“…Using peel force (N/mm) allows for the fact that the method of debonding as described by Fox et al 11 has an element of peel and is not a true shear test, for which the results would be presented in units of stress (MPa). It can be seen that the use of peel or stress does not affect the differences in the rank order between teeth and, as stress (MPa) is the most common unit used to express bond strength, it was used for further data analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This would indicate that bond strength is greatest at the enamel-composite interface. Fox et al 11 suggested that it would be preferable for bonds to fail at the enamel-composite interface as this would reduce the need for removal of composite from the tooth surface at debond following completion of fixed appliance treatment. However, if the bond between bracket and composite is greater than that between composite and enamel, there is an increased possibility of enamel fracture occurring during debond.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation